Phytochemical and Pharmacological potential of Annona cherimola-A Review - Arun Jyothi B,; Venkatesh K,; Chakrapani P,; A Roja Rani, (International Journal of Phytomedicine, 2011)
Several plant remedies have been employed in various medicinal systems for the treatment and management of different diseases. During past several years, there has been growing interest among the usage of various medicinal plants from traditional system of medicine for the treatment of different ailments. Traditional system of medicine consists of large number of plants with various medicinal and pharmacological importances and hence represents a priceless tank of new bioactive molecules. Annona cherimola Miller is a multipurpose tree with edible fruits and is one of the sources of the medicinal products. This review attempts to encompass the available literature on Annona cherimola with respect to its pharmacognostic characters, phytochemical constituents, pharmacological activities and traditional uses.